Customers' readiness for a paradigm shift towards cyberspace: an exploratory investigation in Indian retail banking. (7th May 2021) - Mishra, Brajesh; Prashar, Anupama
The present study is an exploratory investigation in the Indian retail banking sector with the purpose of understanding the drivers of adoption of information and communication technology (ICT) in the retail banking services. The study attempts to achieve the research objective by presenting a triadic view-point of customers, industry, and policymakers. The study is an academic attempt to understand the views of customers, regulators, and banking industry about the traditional brick and mortar, and ATM models, identify various factors that may impact use of ICT to access retail banking services. While the trends in the usage of digital payments including ICT-based delivery channels for accessing retail banking services have been examined to gain demand side perspective, the examination of trends in growth of bank branches and ATMs network have been carried out to verify whether the banks are still focussing on building the brick and mortar, and ATM models of retail banking. It is found that there is a gap between the available infrastructure to support the electronic retail banking platform and the one expected by the retail banking customers for a paradigm shift towards cyberspace.